Waterbird community composition in relation to lake physical traits and wetland limnological conditions in the Amazon basin - Cintra, Renato (Hydrobiologia, 2020)
The mechanisms governing assemblages and the maintenance of biodiversity in tropical environments remain disputed. Two hypotheses were tested for waterbird communities in the Amazonian wetlands: (1) waterbird richness and gradients in species composition differ in Amazonian white- and black-water lakes, and are influenced by variation in lake-to-lake differences in characteristics including area, perimeter, shape, and isolation; (2) waterbird assemblages are also influenced by neighboring water-body richness (rivers, channels, ponds, and other lakes) and location of lakes in the wetlands in relation to the tributary rivers. Bird surveys were conducted using a boat in 264 lakes stretching over 1,000 km of Amazon River floodplains. The hypotheses were tested using multivariate ordination analysis, followed by multiple linear models, to evaluate how bird richness (number of species) and species composition (which species) are affected by abiotic lake characteristics. At a local scale, lake perimeter, area, and shape affected local heterogeneity in species composition of the bird community, whereas at larger scales differences among sites in water-body richness and black- and white-water types were associated with variation in waterbird richness. The patterns found indicate that lake limnological attributes influence local heterogeneity in waterbird communities within Amazonian floodplains. © 2018, Springer International Publishing AG, part of Springer Nature.